2019
DOI: 10.1136/heartjnl-2019-314826
|View full text |Cite
|
Sign up to set email alerts
|

Mid-regional proatrial natriuretic peptide for predicting prognosis in hypertrophic cardiomyopathy

Abstract: Objectives: N-terminal pro-brain natriuretic peptide (NT-proBNP) predicts mortality and the development of heart failure in hypertrophic cardiomyopathy (HCM). Midregional pro-atrial natriuretic peptide (MR-proANP) is a stable byproduct of production of atrial natriuretic peptide. We sought to compare the prognostic value of MR-proANP and NT-proBNP in HCM. Methods:We prospectively enrolled a cohort of patients with HCM from different European centers and followed them. All patients had clinical, ECG and echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Several strategies to explore biomarkers have been pursued in the last years and provided information about circulating long non-coding RNAs [3][4][5] , microRNAs 6,7 , positron emission tomography (PET) 8 or cardiac MRI parameters 9 as well as circulating natriuretic peptides 10 involved into pathophysiology of HCM. First insights into proteomic data from myocardial hypertrophic tissues have been recently provided and several dysregulated proteins in septal myectomies in patients with HCM were described 11 .…”
mentioning
confidence: 99%
“…Several strategies to explore biomarkers have been pursued in the last years and provided information about circulating long non-coding RNAs [3][4][5] , microRNAs 6,7 , positron emission tomography (PET) 8 or cardiac MRI parameters 9 as well as circulating natriuretic peptides 10 involved into pathophysiology of HCM. First insights into proteomic data from myocardial hypertrophic tissues have been recently provided and several dysregulated proteins in septal myectomies in patients with HCM were described 11 .…”
mentioning
confidence: 99%
“…Recently, the predictive value of hematologic biomarkers in patients with HCM has drawn increasing attention. These biomarkers include high-sensitivity C-reactive protein [20], monocyte to HDL-cholesterol ratio [21], red blood cell distribution width [22] and mid-regional proatrial natriuretic peptide [23], all of which are available and novel biomarkers in predicting clinical prognosis in patients with HCM.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP is released when cardiac myocytes are exposed to hemodynamic stress [8] and has a strong association with left ventricular hypertrophy and insufficiency [9,24]. Previous studies have revealed that elevated plasma concentration of NT-proBNP in patients with HCM and found that there was a correlation with more left ventricular outflow tract (LVOT) obstruction, worsening symptoms, and reduced exercise tolerance [23,25]. Although the correlation of elevated NT-proBNP value with more risk of adverse clinical events in patients with HCM has been demonstrated by previous studies [11,25,26], while the present study showed differences in the predictive values of NT-proBNP in patients with HCM, which are due to the highly heterogeneous clinical pattern and the differences in enrolled populations.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with BNP, NT-proBNP is more stable on the merit of its longer half-life ( 23 ). Some studies reported that NT-proBNP was associated with cardiac fibrosis, deterioration of cardiac function, and prognosis in HCM patients ( 26 29 ). According to the 2016 ESC guideline ( 30 ), the NT-proBNP cutoff value is 125 pg/mL, whereas the 2017 AHA criteria suggested using a threshold of 800 pg/mL ( 14 ).…”
Section: Discussionmentioning
confidence: 99%